Cooling of a heated flat plate by an obliquely impinging slot jet - Eren, H; Celik, N (Pergamon-Elsevier Science Ltd, 2006)
Experiments were conducted to determine the effects of some parameters that were crucial in the cooling of a heated flat plate by an obliquely impinging slot jet. The inclination of the jet relative to the surface was varied from 90 degrees to 30 degrees (90 degrees, 60 degrees, 45 degrees and 30 degrees). For Reynolds number of 5860, 8879, and 11606, the variation of local temperatures with respect to dimensionless length (z/L), were investigated. New correlations for local temperatures in terms of Reynolds number, dimensionless distance (z/L) and oblique angle (sin phi) were developed. The displacement region of maximum heat transfer (minimum temperature point) on the plate was measured with respect to geometrical impingement point. Results of experiments indicated that for a given position this displacement increases with increasing the inclination, and the displacement was occurred on compression side of plate. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: confined jet; cooling; heat transfer; rectangular jet